2012
DOI: 10.1002/pon.3040
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of anal cancer screening on HIV‐infected men

Abstract: Anal cancer specific worry increases throughout the screening process. Clear communication prior to procedures about the procedure itself, potential adverse events, the recovery process and non-technical explanations of results should be implemented in anal screening programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Study 1 found those with anal intraepithelial neoplasia (AIN) 2/3; high grade precancerous lesions were no more impacted than others with lesser results 6 . In contrast study 2 found that being referred for HRA led to higher worry and subsequently those with high grade anal intraepithelial neoplasia (HGAIN; equal to AIN 2/3) continued to be worried 31 . The time of most negative impact in study 1 was waiting for results to be given 6 .…”
Section: Psychosocial Impact Of Screeningmentioning
confidence: 73%
See 4 more Smart Citations
“…Study 1 found those with anal intraepithelial neoplasia (AIN) 2/3; high grade precancerous lesions were no more impacted than others with lesser results 6 . In contrast study 2 found that being referred for HRA led to higher worry and subsequently those with high grade anal intraepithelial neoplasia (HGAIN; equal to AIN 2/3) continued to be worried 31 . The time of most negative impact in study 1 was waiting for results to be given 6 .…”
Section: Psychosocial Impact Of Screeningmentioning
confidence: 73%
“…The patients who participated in regular follow up (RF) were two times more likely to agree that 'finding out I had HPV made me feel promiscuous' 30 . Those who were recalled for further investigation rated their anal health lower than those who did not need further investigation 31 .…”
Section: Sexualitymentioning
confidence: 97%
See 3 more Smart Citations